2023
DOI: 10.1002/plr2.20318
|View full text |Cite
|
Sign up to set email alerts
|

‘Newell’ bermudagrass: A public release from the USDA Cynodon collection

E. F. Rios,
Y. Lopez,
P. Munoz
et al.

Abstract: Warm‐season perennial grasses are the backbone of the pasture‐based livestock industry in the lower southeastern United States, and bermudagrass (Cynodon spp.) is the most widely planted forage species, covering ∼15 million ha. The genus Cynodon is native to southern Africa, and germplasm collections possess high genetic and phenotypic variability. The USDA National Plant Germplasm System maintains a collection of bermudagrass plant introductions (PIs) in Griffin, GA, and USDA‐ARS, Tifton, GA, maintains additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Genotypes currently under evaluation maintain the positive attributes of Tifton 85 while overcoming these challenges. Several BSM tolerant lines have been evaluated for pseudostem thickness and have been recently selected for release (Newell [Rios et al, 2023] and 287 [Anderson et al, 2023]). These pseudostems are thinner than Tifton 85 but thick enough to resist BSM larval feeding.…”
Section: Ongoing Grass Breeding and Distribution Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotypes currently under evaluation maintain the positive attributes of Tifton 85 while overcoming these challenges. Several BSM tolerant lines have been evaluated for pseudostem thickness and have been recently selected for release (Newell [Rios et al, 2023] and 287 [Anderson et al, 2023]). These pseudostems are thinner than Tifton 85 but thick enough to resist BSM larval feeding.…”
Section: Ongoing Grass Breeding and Distribution Effortsmentioning
confidence: 99%
“…Multiple trials have found that bermudagrass lines with finer leaves, smaller pseudostems, and denser canopy are more susceptible to BSM damage and consequently have greater production losses (Baxter et al, 2014(Baxter et al, , 2015(Baxter et al, , 2019(Baxter et al, , 2023. The coarse-textured lines that are stargrass or hybrids of bermudagrass and stargrass (i.e., 'Tifton 85', 'Coastcross-II', 'Newell') are more tolerant to the BSM damage (Table 1; Baxter et al, 2019;Baxter et al, 2014;Rios et al, 2023). The yield loss ranges listed in Table 1 represent typical values during the peak damage season for the BSM from mid-summer to early autumn.…”
Section: Differences In Bermudagrass Linesmentioning
confidence: 99%
“…Overall, newer hybrid cultivars are recognized for their superior yield and nutritive value compared to common ecotypes and older releases. Recent releases include Coastcross II, Mislevy, and Newell (Anderson et al, 2024;Rios et al, 2023;Vendramini et al, 2020). These new cultivars build upon initial genetic improvements made by Glenn Burton and others by addressing contemporary issues including establishment time and insect tolerance.…”
Section: Brief History Of Bermudagrassmentioning
confidence: 99%
“…Breeding efforts in Georgia and Florida resulted in the selection of BSM-tolerant lines, which were also evaluated for pseudostem thickness. The cultivar Newell (PI 316510, originally introduced from Ingelheim, Germany) was grown in replicated trials in Florida and showed an average 13% higher accumulation, and similar nutritive value and BSM tolerance to Tifton 85 (Grossman et al, 2021;Rios et al, 2023;de Souza et al, 2020).…”
Section: Damage From the Bsmmentioning
confidence: 99%
“…The genotypes were selected to include two longestablished commercial controls, "FL44" and "Tifton 85", along with seven experimental breeding lines, one of which has subsequently been selected for release under the cultivar name "Newell" (Table 1; Rios et al, 2023). Altogether, the nine genotypes represent a considerable range of available genetic diversity within Cynodon and have been subject to varying degrees of selection pressure on the basis of observed aboveground traits (de Souza et al, 2020;Grossman et al, 2021;Rios et al, 2023). Thus, this experiment is a novel and important source of long-term (5+ year) data to probe whether selection for forage characteristics results in inadvertent tradeoffs in belowground traits with ecosystem-level consequences for SOC.…”
Section: Site Description and Managementmentioning
confidence: 99%